EMISI KARBON BERDASARKAN HISTORICAL BASELINE DENGAN PENDEKATAN STOCK DIFFERENCE PADA VEGETASI HUTAN KOTA MALABAR KOTA MALANG - Zulharman Zulharman (Jurnal Ilmiah Mandala Education (JIME), 2017)
This study aims to determine emissions and stocks of carbon stored in a certain time so that it can be known the effectiveness of vegetation in absorbing carbon in the air. The study was conducted from November 2016 to September 2017. Methods to estimate carbon biomass by using allometric methods. The carbon estimation is done by measuring the diameter of the tree's breast height (diameter at breast height, DBH). by dividing the research location into 2 zones, namely high litter vegetation zone. In each zone is a plot measuring 5m x 40m. Data analysis using historical baseline and stock different methods. From the results of research and discussion that has been done then it can be concluded as follows: Carbon reserves on the surface stored in urban forest Malabar Malang is (1.6718 Ha) is equal to ± 102.96 tons. Annual emissions in the city of Malabar city of Malang based on the historical baseline is 2.13 tons. The sengon tree is the tallest and largest-diameter tree in the Malabar forest, making it the greatest carbon-storage force because it is not blocked by other trees or vegetation, the sengon tree is also easy to live under conditions of growing not too high. Therefore, it is suitable to be planted in urban green open space to absorb carbon in the atmosphere that damages the environment and human health.